Assessment of winter garlic collection according to productivity and biochemical composition in the conditions of the Kirov region - O. A. Cheglakova; A. V. Denisova; V. M. Motov (Аграрная наука Евро-Северо-Востока)
The article presents the results of studying the winter garlic collection according to a complex of traits in the conditions of the Kirov region in order to identify for the breeding process promising forms with high productivity, good biochemical composition, suitability for mechanized sowing. During the study, planting with bulblets was used as the most common method of reproduction. In 2019-2020, fifteen varietal samples of winter garlic of different ecological and geographical origin adapted to local growing conditions were studied. Overwintering of all samples was 100 %. Varietal samples No. 154, 96, 116, 136, 155 and the standard variety Lyubov are suitable for mechanized sowing (clove weight is 5 g or more). According to the yield relative to the Lyubov standard variety (0.82 kg/m2 ), variety sample No. 115 stood out (1.02 kg/m2 ), LSD 05 = 0.16 kg/m2 . The maximum height of a scape of 122.5 cm was noted in the Kirovsky variety. According to the size of the bulblets, varietal samples No. 135 and 140, having 0.15 g weight of 1 bulbet were distinguished. According to the biochemical composition, the following varietal samples were selected: No. 155 having a combination of an increased content of dry matter (46.24 %) and sugar (15.82 %); No. 135 having a high content of ascorbic acid (13.20 mg%). The sample No. 154 also had a complex of valuable traits: the maturation 12 days earlier relative to the control and other samples; the highest leaf length and width (51.9 and 2.3 cm, respectively); the largest number of scapes (6 pieces); a high yield of 0.94 kg/m2 (at the control level); a maximum average clove weight (7 g).